Innovative Higher Education Approaches for Power System Courses - Ettore Bompard; Abouzar Estebsari; Andrea Mazza; Enrico Pons; Lorenzo Solida (MDPI AG, 2023)
Higher education plays a crucial role in modern society and in emerging energy systems, due to the rising complexity of the phenomena and the interplay among various layers (physical, cyber, social and economic). To cope with this context, universities need to develop new visions and tools for education and training. Real-time simulation (RTS) is emerging as a novel and effective approach to analyzing power system aspects, and this characteristic can be effectively used in power system courses. Hence, after the presentation of the basics about the RTS, the paper will show the advantages of employing RTS for teaching activities. Finally, two examples of didactic activities involving RTS at Politecnico di Torino will be presented. In fact, RTS is part of both multi-disciplinary projects (where students with different backgrounds can face the issues affecting the protection and control of power systems) and the course "Electrical systems and safety", where RTS is used to study the behavior of voltage transformers in saturation.